Strategies in activating lymphatic system to promote lymph flow on lymphedema symptoms in breast cancer survivors: A randomized controlled trial - Du, Xinwen; Li, Yuan; Fu, Lan; Chen, Huaying; Zhang, Xiaoxia; Shui, Yuping; Zhang, Aihua; Feng, Xianqiong; Fu, Mei Rosemary (Frontiers in Oncology, 2022)
Background: Many breast cancer survivors face long-term postoperative challenges as a result of developing lymphedema symptoms and chronic lymphedema. The-Optimal-Lymph-Flow (TOLF) program is an intervention based on physiological-cognitive-behavioral principles that teaches patients self-management strategies to activate lymphatic system and promote lymph flow to decrease lymphatic pain, reduce the risk and severity of lymphedema. Objective: The purpose of this pilot clinical trial was to evaluate the use of TOLF program as an early intervention on improving lymphedema symptom experience (i.e., symptom number, symptom severity, symptom distress, and the impact of symptoms on patients’ activities of daily living) and optimizing lymph fluid levels (measured by the arm volume differences) among breast cancer survivors. Methods: This study is a parallel, randomized clinical trial. A total of 92 breast cancer patients were randomly assigned to either the TOLF intervention group or the control group that to promote arm mobility. Data were collected at baseline and end of the trial at the 3-month post intervention. The Breast Cancer and Lymphedema Symptom Experience Index was used to measure lymphedema symptom experience. Anthropometric measurements were used for circumferential arm measurements. Generalized linear mixed-effects models were used to evaluate the trial outcomes. Results: Significant improvements of lymphedema symptom experience were found in patients in the TOLF intervention group in comparison with patients in control group: the number of lymphedema symptoms (P<0.001) and the severity of lymphedema symptoms (P<0.001) as well as the impact of symptoms on patients’ daily living function (P<0.001). Patients in both groups showed improvements in all study outcomes over the 3 months, whereas those in the TOLF group gained greater benefits in reducing the number and severity of lymphedema symptoms. Moreover, the TOLF group had significantly fewer patients with ≥5% arm volume differences ([5/45] vs [13/43], P=0.035) at the study endpoint. Conclusion: Findings of the study demonstrated positive outcomes of relieving lymphedema symptom experience, optimizing arm circumference and halting the progression of lymphedema status in breast cancer survivors receiving TOLF intervention during early postoperative time. Given its feasibility, acceptability, and effectiveness, this program may be incorporated in routine breast cancer care.